Planning and Food Sovereignty in Conflict Cities: Insights From Urban Growers in Srinagar, Jammu and Kashmir. Issue 2 (3rd April 2023) - Raja, Samina; Parvaiz, Athar; Sanders, Lanika; Judelsohn, Alexandra; Guru, Shireen; Bhan, Mona; Osuri, Goldie; Tak, Mehroosh; Mui, Yeeli; Frimpong Boamah, Emmanuel
Abstract: Problem, research strategy, and findings: Protracted political conflicts disrupt people's lives, including their ability to feed themselves. Urban planning, operating within the ambit of the state, impacts food systems in conflict cities. We examine the confluence of planning and political misgovernance on food sovereignty in conflict cities. We do so by documenting the experiences of urban growers who cultivate, eat, and distribute indigenous greens ( haakh ) in the city of Srinagar in the Himalayan belt of Jammu and Kashmir, the site of a protracted conflict. Experiences of growers were analyzed within the context of the city's complex urban planning landscape. Empirical methods included qualitative interviews of urban growers ( n = 40) and review of land use plans and policies. We found that haakh production ensured access to affordable, nutritious, and culturally celebrated greens for haakh growing households. That said, intersecting burdens from undemocratic governance and militarism (from India), weak forms of local planning (within Srinagar), and climate change threaten urban growers' work, and imperils food sovereignty. Completing a study in a conflict region was extraordinarily challenging. The study's generalizability is limited by its short duration and small sample size—the inductive findings set the stage for future research. Takeaway for practice: Conflict cities are a reminder that urban planning is anything but technical. Planning curricula must prepare future planners for the politics of planning. Planners in conflict cities are in liminal positions—between the state and the public . To the best of their ability, planners in conflict cities such as Srinagar have to protect smallholder growers' control of their food system, especially over land and water. The monitoring, recording, and suspension of contested or undemocratic land conversions, land grabs, or land transfers without full consent of indigenous and local peoples ought to be a local and international policy priority.